2021
DOI: 10.3390/cancers13215461
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Alters the Energy Metabolism of Stromal Cells and Could Promote Bladder Cancer Progression

Abstract: Bisphenol A (BPA) is an endocrine-disrupting molecule used in plastics. Through its release in food and the environment, BPA can be found in humans and is mostly excreted in urine. The bladder is therefore continuously exposed to this compound. BPA can bind to multiple cell receptors involved in proliferation, migration and invasion pathways, and exposure to BPA is associated with cancer progression. Considering the physiological concentrations of BPA in urine, we tested the effect of nanomolar concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Indeed, mitochondrial dysfunction is often associated with known pathologies [ 31 , 32 , 33 ]. For example, Pellerin et al showed that cancer-associated fibroblasts (CAFs) exhibit modified metabolism, with increased basal and maximal glycolysis (ECAR) compared to normal fibroblasts [ 34 ] (also reviewed in [ 35 , 36 , 37 ]). The results obtained in the current study indicated that the ATP production through mitochondrial respiration and mitochondrial capacity tended to be greater in the cell culture conditions using SFM compared to FBSCM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mitochondrial dysfunction is often associated with known pathologies [ 31 , 32 , 33 ]. For example, Pellerin et al showed that cancer-associated fibroblasts (CAFs) exhibit modified metabolism, with increased basal and maximal glycolysis (ECAR) compared to normal fibroblasts [ 34 ] (also reviewed in [ 35 , 36 , 37 ]). The results obtained in the current study indicated that the ATP production through mitochondrial respiration and mitochondrial capacity tended to be greater in the cell culture conditions using SFM compared to FBSCM.…”
Section: Discussionmentioning
confidence: 99%
“…Mito Stress media consisted of XF Base Medium supplemented with 2 mM L-glutamine, 1 mM sodium pyruvate (Wisent Bioproducts Inc.) and 10 mM D-(+)-glucose (Millipore Sigma). The extracellular acidification rate (ECAR), representative of glycolytic metabolism, and the oxygen consumption rate (OCR), representative of mitochondrial respiration, were determined using the XFe Extracellular Flux Analyzer (Agilent/Seahorse Bioscience) [ 20 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was previously demonstrated that the energy metabolism of healthy bladder fibroblasts decreased after chronic exposure to physiological concentrations of BPA. In contrast, BPA-exposed cancer-associated fibroblasts (CAFs) displayed an increased glycolytic metabolism, leading to extracellular acidification [ 20 ]. This enhanced acidification can lead to the inhibition of immune cells, such as monocytes, as well as reorganization of the extracellular matrix [ 21 , 22 ], thus potentially promoting bladder cancer progression [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mito Stress media contained XF Base Medium supplemented with 2 mM L-glutamine, 1 mM sodium pyruvate (Wisent Bioproducts Inc.) and 10 mM D-(+)-glucose (Millipore Sigma, Oakville, ON, Canada). The extracellular acidification rate (ECAR), representative of the glycolytic capacity, and the oxygen consumption rate (OCR), representative of the mitochondrial respiration, were determined using the XFe Extracellular Flux Analyzer (Agilent/Seahorse Bioscience) [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%